2017
DOI: 10.1177/1326365x17716707
|View full text |Cite
|
Sign up to set email alerts
|

Experiential Learning in the Social and Mobile-first Student Newsroom

Abstract: This paper is an exploration of student feedback to their participation and learning in the social and mobile-first multimedia newsroom run as part of the Bachelor of Journalism degree at the University of Wollongong, Australia. The paper draws on student responses to an online survey carried out in the wake of the final-year newsroom subject. Acknowledging one of the main aims of journalism, newsroom curriculum is to present ‘real-world’ experiences as authentically as possible. The paper explores the student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
2
0
3
Order By: Relevance
“…In thematic analysis, codes are used as the building blocks of themes, which provide a framework for the researcher to reveal their findings as more than summarized data, but interpreted data (Braun & Clarke, 2006). Burns (2017) used a similar form of content analysis in their study of experiential learning in student newsrooms. In their study of journalism students’ perceptions of fake news, Bhaskaran et al (2019) conducted focus groups of five or six participants, and then thematically coded the transcripts.…”
Section: Research Questions Participant Population and Methodsmentioning
confidence: 99%
“…In thematic analysis, codes are used as the building blocks of themes, which provide a framework for the researcher to reveal their findings as more than summarized data, but interpreted data (Braun & Clarke, 2006). Burns (2017) used a similar form of content analysis in their study of experiential learning in student newsrooms. In their study of journalism students’ perceptions of fake news, Bhaskaran et al (2019) conducted focus groups of five or six participants, and then thematically coded the transcripts.…”
Section: Research Questions Participant Population and Methodsmentioning
confidence: 99%
“…A study at the University of Wollongong in Australia explored student feedback after participating in the mobile phone newsroom run as part of their Bachelor of Journalism course. The study demonstrated that through a consistent and structured exposure to newsroom practices, students understood the power of the mobile multimedia newsroom and the value of an authentic real-world learning environment (Burns, 2017).…”
Section: English Writing and Video Production Skillsmentioning
confidence: 95%
“…Bajo este marco, los MCU se abocan principalmente a los enfoques constructivistas: algunos estudios hacen referencia al aprender haciendo (Pain, et al, 2016), simulación y aprender a aprender (Larrondo y Peña, 2018), aprendizaje experiencial (Burns, 2017), aprendizaje por proyectos (Sánchez y Fernández, 2015), o aprendizaje servicio (Nogales-Bocio y Álvarez, 2020). En cualquier caso, los MCU no buscan enfrentar al estudiante a cuestiones reales sin un componente pedagógico, ya que es necesario que estas situaciones se acompañen de una autorreflexión crítica, que permita cerrar la brecha entre la práctica y la teoría para construir el conocimiento en una profesión tan dinámica como el periodismo (Deuze, 2000;Kronstad, 2016).…”
Section: Los Mcu Como Escenarios De Aprendizajeunclassified
“…Son muchos los estudios que han reflexionado sobre la importancia de aprender haciendo periodismo, en tanto que la confrontación del estudiante con situaciones propias de la profesión tiene un profundo impacto en los participantes y en su propia visión sobre el relacionamiento y el rol que deben asumir ante la sociedad (Burns, 2017;Pain et al, 2016). Es tal la relevancia de este ámbito que, incluso, configura un enfoque experiencial que abarca a todos los procesos de enseñanza y aprendizaje, tal y como propuso la Universidad de Missouri, institución que centró su formación profesional en periodismo a partir del desarrollo de las habilidades y la ética de los estudiantes (Folkerts, 2014).…”
Section: Introductionunclassified